Public Service Innovation: A Comparative Study of Serang and Bogor Cities in Public Service Delivery - Saprudin, Saprudin; Zulmasyhur, Zulmasyhur (Journal of Governance, 2024)
The dissimilarities in public service innovation strategies between the Investment and Integrated One-Stop Service Offices of Serang City and Bogor City reveal critical implications for governance and policy research. The emphasis in Serang City on employee training to enhance service quality highlights the need for capacity-building initiatives in resource-constrained settings, while Bogor City’s focus on leveraging advanced technology underscores the role of digital transformation in improving service accessibility. These differences indicate that tailored approaches to innovation are essential based on local context and resource availability. Moreover, Bogor City’s effective budget management and stronger community participation emphasize the importance of participatory governance and fiscal discipline in driving successful public service delivery. The shared advancements in efficiency demonstrate that strategic reforms can reduce costs and improve productivity, even amid constraints. Based on these results, more research should be done on frameworks that combine maximizing resources, involving the community, and using new technologies to make public service innovation last and benefit everyone.